PERANCANGAN DAN ANALISIS SISTEM PENDETEKSI INTRUSI BERBASIS NETWORK INTRUSION DETECTION SYSTEM (NIDS) PADA SISTEM KEAMANAN JARINGAN KOMPUTER - Ferrianto Gozali; Achmad Lucky Setiaji (Jetri : Jurnal Ilmiah Teknik Elektro, 2013)
Abstract Network intrusion detection system is a system that can detect illegal accesses or intrusions happened in a computer network. Actually, there are many types of intrusion detection systems and the differences are based on how network administrators implement the system to secure the network. In this study, the system called Network Intrusion Detection System or NIDS in brief, is used to design and implement the intrusion detection system in the network model design. Intrusion detection system will utilize the snort application that serves as a sensor and detection server and be implemented in a network model that has been designed previously. The performance of the system is investigated through the monitoring of the use of disk space, memory usage and cpu usage of the system during intrusion detection identification process. Three different intrusion scenarios such as Portscanning, ICMP flooding and SYN flooding is performed to see the effect in the system's performance. During the test, the use of disk space still has not shown any significant use, due to the detection time limit used in this study was too short. However, the difference in memory